Sistem Pendingin Wire &Tube Transformator Frekuanesi 50-60 Hz pada Prototipe Electric Arc Furnace (EAF) - Angga Tegar Setiawan; Ahmadi Ahmadi; Fahrul Fahrul; Jumaddil Hair (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The Electric Arc Furnace (EAF) prototype at the Morowali Metal Industry Polytechnic has the main component in the form of a transformer that generates heat actively. The increase in temperature that occurs in the transformer is caused by continuous loading. In addition, a significant and relatively high temperature rise in the transformer, can reduce the performance of the transformer. This research will design a transformer cooling system on the EAF prototype. The temperature of the transformer will be maintained at a certain temperature until there is no longer an increase in temperature due to loading. The wire-tube cooling system in the transformer uses water and transformer oil as the cooling medium. Regulating the flow rate of the water fluid in the copper pipe is expected to be able to further optimize the cooling process in the transformer. The results show that the design of the wire-tube cooling system is able to release the temperature of the transformer oil with a heat transfer rate that varies according to the flow rate of the cooling water fluid. Experiments carried out for 30 minutes resulted in a heat transfer rate of Qu 760.5 kJ/s with a water flow rate of 2.5 liters/minute, Qu 1661.2 kJ/s with a water flow rate of 5 liters/minute, Qu 2558.5 kJ/kg with a water flow rate of 5 liters/minute. the water flow rate is 7.5 liters/minute and Qu 3213.9 kJ/kg with a water flow rate of 9.20 liters/minute, this shows that the higher the water flow rate, the higher the heat transfer.